A coherent framework for non-ionising radiation protection. (12th January 2022) - Tinker, Rick; Abramowicz, Jacques; Karabetsos, Efthymios; Magnusson, Sigurður; Matthes, Rüdiger; Moser, Mirjana; Niu, Shengli; O'Hagan, John; van Deventer, Emilie
Abstract: A coherent and overarching framework for health protection from non-ionising radiation (NIR) does not currently exist. Instead, many governments maintain different compliance needs targeting only some NIR exposure situations. An international framework developed by the World Health Organization would promote a globally consistent approach for the protection of people from NIR. Designed based on decades of practical experience the framework provides guidance on establishing clear national health and safety objectives and how they should be achieved. It supports multisectoral action and engagement by providing a common language and systematic approach for managing NIR. The framework should allow governments to respond to policy challenges on how to achieve effective protection of people, especially in a world that is rapidly deploying new NIR technologies. In this paper the concepts and key features are presented that underpin the framework for NIR protection, including examples of implementation.